(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Based on statistical data, the essay discusses the significance of private investment in the economy and how it contributes to the growth of international economic activity. The dynamics of foreign trade turnover, the growth of export activity of the topic of foreign economic activity, and the issue of the development of the export-oriented economy in the Republic of Uzbekistan are all examined.